SCHIZOAFFECTIVE DISORDER WITH MANIC TYPE : A CASE REPORT - Kharisma Putra, A.A. Gede Ocha Rama (E-Jurnal Medika Udayana; vol 3 no 3 (2014):e-jurnal medika udayana, 2014)
Schizoaffective disorder is a disease with persistent psychotic symptoms, such as hallucinations or delusions, occurs together with mood disorder such as depression, manic, or mixed episodes. Schizoaffective disorder is estimated to occur more frequently than bipolar disorder. A psychotic disorder with symptoms of schizophrenia and manic air equally prominent in one episode of the same disease. This report describes the case of b schizoaffective disorder with manic type in women aged 42 years. These patients get therapy is pharmacotherapy Carbamazepine 2x200 mg orally and Stelazine 2x5 mg orally.
Keywords: schizoaffective, mood